POPULARISASI IHYÂ ‘ULÛM AL-DÎN DI NUSANTARA: MELACAK AKAR HISTORIS MELALUI SUDUT PANDANG SUFISTIK DAN HADIS - In’amul Hasan (UIN ANTASARI BANJARMASIN, 2021)
al-Ghazali as the author of the Ihyâ ‘Ulûm al-Dîn has an interesting life journey background. He had been an ahlu al-ra'yi (philosopher) then turned into a Sufi in his old age. This change is indicated by several his books (kitab). One of them is Ihyâ ‘Ulûm al-Dîn. This literature later became popular in the Nusantara. Ihyâ ‘Ulûm al-Dîn is also used as the main reference for a Muslim's life guide. However, behind the popularity of this book, many hadith scholars (muhadditsîn) gave controversial comments on the hadis that contained in this book. Although there are many critical comments, the popularity of Ihyâ ‘Ulûm al-Dîn has not been forgotten in Nusantara, and it still exists today. This was seen during the Musabaqah Qiraah al-Kutub (MQK). At the event, this book was used as one of the books contested for the branch of morality. This article discusses the reasons or causes for this book to still exist, especially in Nusantara. The research was conducted with a historical approach. Then the history of the arrival of Islam to Nusantara will be explored, which is accompanied by Sufi and muhadditsîn interpretations of the hadis that contained in this book. So this article will show the popularization of Ihyâ 'Ulûm al-Dîn in Nusantara.Imam al-Ghazali sebagai pengarang kitab Ihyâ ‘Ulûm al-Dîn memiliki latar belakang yang menarik. Ia pernah menjadi ahlu al-ra’yi (filsuf) kemudian beralih menjadi seorang sufi pada masa tuanya. Perubahan tersebut ditunjukan oleh beberapa karangannya (kitab). Salah satunya adalah Ihyâ ‘Ulûm al-Dîn ini. Literatur inilah di kemudian hari menjadi populer di Nusantara. Ihyâ ‘Ulûm al-Dîn juga dijadikan sebagai rujukan utama panduan hidup seorang muslim. Namun, dibalik kepopuleran kitab ini, banyak ulama hadis (muhadditsîn) memberikan komentar yang kontroversial terhadap hadis-hadis yang dimuat dalam kitab ini. Walaupun komentar miring tersebut banyak, kepopuleran kitab Ihyâ ‘Ulûm al-Dîn tidak lusuh di Nusantara, bahkan bisa bertahan hingga saat ini. Hal itu terlihat pada saat Musabaqah Qiraah al-Kutub (MQK). Pada event tersebut, kitab ini dijadikan sebagai salah satu kitab yang dilombakan pada cabang akhlak. Artikel ini membahas alasan atau penyebab kitab ini tetap eksis, terutama di Nusantara. Penelitian dilakukan dengan pendekatan historis. Maka sejarah masuknya Islam ke Nusantara akan digali, yang diiringi dengan interpretasi sufi dan muhadditsîn terhadap hadis-hadis yang ada dalam kitab ini. Sehingga artikel ini akan menunjukan popularisasi Ihyâ ‘Ulûm al-Dîn di Nusantara